â€œREPRESENTASI PEREMPUAN SEBAGAI IDEOLOGI DALAM CERITA DARI BLORA KARYA PRAMUDYA ANANTA TOERâ€ (Sebuah Kajian Feminisme) - Maryanah, Imas (Humanus, 2014)
The world’s increasing feminist activism has grown gender studies, both in real life and literature. Gender studies in several universities in Indonesia provide a lot of essential information about women’s position that are constructed to be marginal and unfortunate in social life. Critical feminist literature has improved better along with the women’s awareness of their rights that are robbed by patriarchy, which is created to marginalize them. Apparently their have important role and contribution in improving life quality.‘Cerita dari Blora’ (A story from Blora), written by Pramudya Ananta Toer, tells stories about women in Blora, Central Java. Economic, social, political, and cultural disorder in the country has increased the abuse of women as reflected in the dry and infertile land of Blora. There is no hope for the people who are humbled by the harsh and complicated life. Several female protagonists in the story are described to suffer in the patriarchal system that dominates the ideology of Blora community. There is only one strong woman in the story, called ‘Ibu’ (mother) who changes and lifts women’s status. The women’s fight will be continued by mothers for the blossoming of the next generation.Key words: feminism, gender, patriarchy, women